Quality of life of persons with permanent colostomy: a phenomenological study - Alwi,Fahrizal (2018)
ABSTRACT Objectives: To describe the experiences of persons with permanent colostomy regarding their quality of life. Methods: The study design used descriptive phenomenology following the approach of Collaizzi. There were 12 participants who qualified using purposive sampling based on the inclusion criteria.The data generated were in-depth interviews. Analysis and interpretation used verbatim descriptions. Results: The research data revealed seven themes, namely: limitation in daily living activities, limitations in marital relations and social relationship with others, negative feelings about having the colostomy, financial difficulties, increasing demands of living with colostomy, changes in the needs of rest, physical and expectation of complications, and hoping to live a normal life after colostomy. Conclusion: This study revealed that persons with permanent colostomy experience difficulties and limitations pertaining to daily living activities, including marital and social relations. Importantly, they experience psychological concerns, e.g. having negative feelings about ways of living their lives, including financial difficulties and adjusting to new ways of living. However, there is always the hope to live a normal life. This study provides an understanding of the quality of life of persons with permanent colostomy, allowing nurses to provide appropriate nursing care.